Taking a wellbeing years approach to policy choice. (5th October 2020) - De Neve, Jan-Emmanuel; Clark, Andrew E; Krekel, Christian; Layard, Richard; O'Donnell, Gus
Abstract : Decisions about lockdown should consider people's wellbeing as a guide